2020
DOI: 10.1186/s40364-020-00219-y
|View full text |Cite
|
Sign up to set email alerts
|

A radiomics-based model on non-contrast CT for predicting cirrhosis: make the most of image data

Abstract: Background To establish and validate a radiomics-based model for predicting liver cirrhosis in patients with hepatitis B virus (HBV) by using non-contrast computed tomography (CT). Methods This retrospective study developed a radiomics-based model in a training cohort of 144 HBV-infected patients. Radiomic features were extracted from abdominal non-contrast CT scans. Features selection was performed with the least absolute shrinkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
(40 reference statements)
0
25
0
Order By: Relevance
“…Nomogram modelling has been used effectively in a number of studies. 29,30 We recommend that patients who are judged to be at high risk using our diagnostic model should have supplemental CT scans before surgery to confirm the diagnosis and rule-out abdominal metastasis of GBC. Additionally, compared with artificially assigning risk factors, assigning corresponding weights to variables through statistical methods may result in more objective extraction of information from clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Nomogram modelling has been used effectively in a number of studies. 29,30 We recommend that patients who are judged to be at high risk using our diagnostic model should have supplemental CT scans before surgery to confirm the diagnosis and rule-out abdominal metastasis of GBC. Additionally, compared with artificially assigning risk factors, assigning corresponding weights to variables through statistical methods may result in more objective extraction of information from clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…All the indicators included in our model can be obtained through physical examination of outpatient. Modelling by using nomograms has been used in a number of studies and has been shown to be effective [29] [30]. We recommend that patients who are judged to be at high risk through our diagnostic model could be supplemented with CT scans before surgery to further con rm the diagnosis and rule out gallbladder cancer abdominal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Regions of interest (ROIs) were selected in the liver of all patients by two radiologists using 3D slicer (version 4.8.0; http://www.slicer.org ) [ 17 ]. The ROIs were manually segmented along the tumor contour on each transverse section.…”
Section: Methodsmentioning
confidence: 99%